Northern Exposures : An Adventuring Career in Stories and Images - Waterman, Jonathan (Book collections on Project MUSE., 2013)
"Waterman's profound respect for the northern lands burns on every page, and his photos and essays prove to us that there is still beauty in this world-beauty worth fighting for."--Robert RedfordNorth of the sixtieth parallel, the sun shines for less than six hours in the winter, and towering mountains are the only skyscrapers. Pristine waters serve caribou, moose, and bears in an unbroken landscape. At any given moment in this spectacular scenery, there's a chance that Jonathan Waterman is present, trekking across the land. A masterful adventurer, Waterman has spent decades exploring the farth